Heterologous expression of Mus musculus immunoresponsive gene 1 (irg1) in Escherichia coli results in itaconate production - Vuoristo, Kiira S.; Mars, Astrid E.; van Loon, Stijn; Orsi, Enrico; Eggink, Gerrit; Sanders, Johan P. M.; Weusthuis, Ruud A. (Frontiers in Microbiology, 2015)
Itaconic acid, a C5-dicarboxylic acid, is a potential biobased building block for the polymer industry. It is obtained from the citric acid cycle by decarboxylation of cis-aconitic acid. This reaction is catalysed by CadA in the native itaconic acid producer Aspergillus terreus. Recently, another enzyme encoded by the mammalian immunoresponsive gene 1 (irg1), was found to decarboxylate cis-aconitate to itaconate in vitro. We show that heterologous expression of irg1 enabled itaconate production in E. coli with production titres up to 560 mg/L.